2009
DOI: 10.1158/0008-5472.can-08-4120
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Lentiviral-Mediated Choline Kinase Targeting in a Human Breast Cancer Xenograft

Abstract: Elevated phosphocholine (PC) and total choline (tCho) metabolites are widely established characteristics of most cancer cells, including breast cancer. Effective silencing of choline kinase (chk), the enzyme that converts choline to PC, is associated with reduced tumor growth. The functional importance and down-regulation of chk using RNA interference has been previously established. Here, we report on the preclinical evaluation of lentiviral vector-mediated downregulation of chk using short hairpin RNA (shRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 22 publications
(36 reference statements)
4
92
0
Order By: Relevance
“…Although our approach illustrates tissue heterogeneity, the use of microdissection techniques and larger samples size may reduce the variation observed in the presented results. In a number of studies, CHKA has been shown to mediate cellular proliferation, transformation, and carcinogenesis, and mediation of this target using siRNA and smallmolecule inhibitors suggests inhibition of tumor growth (11,16,18,40,41). As indicated, we further observed in clinical samples and endometrial cancer cell lines, a significant increase in the mRNA expression of enzymes of the phosphatidylcholine deacylation pathway; GPCPD1, LYPLA1, and LYPLA2.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although our approach illustrates tissue heterogeneity, the use of microdissection techniques and larger samples size may reduce the variation observed in the presented results. In a number of studies, CHKA has been shown to mediate cellular proliferation, transformation, and carcinogenesis, and mediation of this target using siRNA and smallmolecule inhibitors suggests inhibition of tumor growth (11,16,18,40,41). As indicated, we further observed in clinical samples and endometrial cancer cell lines, a significant increase in the mRNA expression of enzymes of the phosphatidylcholine deacylation pathway; GPCPD1, LYPLA1, and LYPLA2.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, overexpression of CHKA (6)(7)(8) and abundance of choline metabolites (13)(14)(15) have been shown to be prognostic in a number of cancers including prostate, breast, lung, and ovarian cancer. More recently inhibition of CHKA, both by shRNA and small-molecule inhibitors, has been shown to have both an antimitogenic and antiproliferative effects in vitro and in vivo (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with studies that suggested a positive correlation between Ki-67 score and shorter survival. 40,41 We have previously shown that CRLX101 treatment inhibited expression of CaIX in a tumor sections. Also the expression of CaIX was lower in the sample from the patient with longer survival duration as compared to the other.…”
Section: Numerous Preclinical and Clinical Studies Have Demonstrated mentioning
confidence: 99%
“…The ChoCCs constitute important building blocks in cell membranes and are elevated, in several malignancies (8,9), including prostate cancer (10), due to altered phospholipid metabolism. When using gene therapy to silence the enzyme choline kinase converting Cho to PC, a reduction of cell proliferation and tumor growth was shown in breast cancer cell lines (11). The prostate is highly specialized for the production and secretion of citrate, which is used as an energy supply for sperm.…”
Section: Introductionmentioning
confidence: 99%